KAJIAN KANDUNGAN LOGAM BERAT MERKURI (Hg) PADA KERANG AIR TAWAR (Anodonta sp) DI KAWASAN HILIR SUB DAS KRUENG MEUREUBO, ACEH BARAT - Munandar Munandar; Alwis Alamsyah (JURNAL PERIKANAN TROPIS, 2016)
One source of mercury pollution came from gold mining was done by the community from gold processing through amalgamation. Heavy metals that present in the waters will undergo deposition process and accumulate in marine animals then end up in humans. Meureubo upstream region is one of the locations that still carried out the gold mining activities used mercury. That condition is one potential factor that can contaminate the waters. This study was conducted in October-November 2014. Sampling was taked in Meureubo River and the mercury content analysis was carried out in the Laboratory of Research and Standardization Industry (Baristan) Banda Aceh. The laboratory analysis results showed that the total mercury (Hg) of heavy metals in the freshwater mussels samples (Anodonta sp) on RP station is 0,074 ppm, PP illustrates 0,042 ppm and PA confirms 0.304 ppm. Furthermore, the total mercury (Hg) of heavy metals in the sample freshwater on RP station around 0.0005085 mg/l, PP 0.0001792 mg/l and PA 0.0006711 mg/l. The results showed that the samples of freshwater mussels (Anodonta sp) and the water samples which taken at three stations (Rantau Panjang, Pasi Pinang, Pasi Aceh) were positive for mercury (Hg).